Social Media as a Tool in Improving Public Relations in the Digital Marketing Era: Qualitative Insights - Pranata, Wahyu; Valevi, Syah; Habibullah, Mhd; Sari, Rika; Nofirda, Fitri (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The presence of social media in today’s society brings enormous benefits, especially in the digital economy. Social networks can indeed be called a popular phenomenon that attracts the attention of many people. In many of his works, experts have given many different definitions of the technologies that society still needs today. Business development in Indonesia is very rapid and continues to progress. Based on the method used, this research is qualitative using library research and descriptive qualitative methods. This research refers to previous research that will be discussed again to find something that has not been known before. Research that is library research and descriptive qualitative Based on the results of the analysis that refers to the results of previous research, it can be said that social media has an important role in supporting overall activities, one of which is being able to establish public relations relationships with customers social media has become a platform that can provide benefits that can facilitate business people to interact, Promote, introduce, and brand products to be sold online media play an important role in almost all levels of society, sharing information to find information. The role of Public Relations is great for every business, not only acting as an image developer but also marketing products to the public. Based on the results of the analysis that refers to the results of the previous research, it can be said that an important role in supporting overall activities is to be able to establish public relations relationships with customers.